Minimal effects of UVB radiation on Antarctic diatoms over the past 20 years - Andrew McMinn; Heijins, H; Hodgson, D (1994)
It has been suggested(1-3) that increased springtime UVB radiation caused by stratospheric ozone depletion is likely to reduce primary production and induce changes in the species composition of Antarctic marine phytoplankton. Experiments conducted at Arthur Harbour in the Antarctic Peninsula revealed a reduction in primary productivity at both ambient and increased levels of UVB (ref. 4). Laboratory studies have shown that most species in culture are sensitive to high UVB levels, although the level at which either growth or photosynthesis is inhibited is variable (5,6). Stratospheric ozone depletion, with resultant increased springtime UVB irradiance, has been occurring with increasing severity since the late 1970s. Thus the phytoplankton community has already experienced about 20 years' exposure to increasing levels of UVB radiation. Here we present analyses of diatom assemblages from high-resolution stratigraphic sequences from anoxic basins in fjords of the Vestfolds Hills, Antarctica. We find that compositional changes in the diatom component of the phytoplankton community over the past 20 years cannot be distinguished from long-term natural variability, although there is some indication of a decline in the production of some sea-ice diatoms. We anticipate that our results are applicable to other Antarctic coastal regions, where thick ice cover and the timing of the phytoplankton bloom protect the phytoplankton from the effects of increased UVB radiation.